2008
DOI: 10.1603/0022-2585(2008)45[891:narbia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Arthropod Repellent, BioUD, Is an Efficacious Alternative to Deet

Abstract: For >50 yr, N,N-diethyl-3-methylbenzamide (deet) has been the standard for arthropod repellents and has been an important tool to protect people from disease agents carried by ticks, mosquitoes, and other arthropods. However, some people avoid using deet because of concerns about adverse health effects. In 2007, a new repellent, BioUD, with the active ingredient 7.75% 2-undecanone, originally derived from wild tomato (Lycopersicon hirsutum Dunal f. glabratum C. H. Müll) plants, was registered by the U.S. Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Two-choice bioassay: BioUD vs. DEET (head-to-head comparison) Witting-Bissinger et al (2008) showed that BioUD Ò with 7.75% 2-undecanone in head-tohead comparisons using filter paper choice assays was more repellent than 15% DEET against unfed American dog tick adults. In the current study, dose-response studies were conducted to better assess the relative effectiveness of the two repellents (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-choice bioassay: BioUD vs. DEET (head-to-head comparison) Witting-Bissinger et al (2008) showed that BioUD Ò with 7.75% 2-undecanone in head-tohead comparisons using filter paper choice assays was more repellent than 15% DEET against unfed American dog tick adults. In the current study, dose-response studies were conducted to better assess the relative effectiveness of the two repellents (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance of L. hirsutum f. glabratum to insect herbivory is due in part to the presence of 2-undecanone (Kennedy 2003). Witting-Bissinger et al (2008) showed BioUD Ò was an efficacious repellent against D. variabilis in laboratory studies on treated human skin, cloth, and filter paper. The rat acute oral and dermal toxicity and rabbit dermal irritation toxicity tests resulted in BioUD Ò being rated as category IV (the lowest toxicity level) by the EPA.…”
Section: Introductionmentioning
confidence: 99%
“…Because the presence of a host, the specific field conditions under which a repellent might be used and/or the specific assay conditions used for repellent testing might affect repellent performance, more research is needed to fully understand the activity of BioUD compared with other available technologies. However, the studies described in this paper and others 18,19 on and off the skin of human hosts thus far suggest that BioUD is an efficacious alternative to DEET and other commercially available arthropod repellents for use against ticks. …”
Section: Discussionmentioning
confidence: 72%
“…27 Previously we showed that BioUD applied to cotton cheesecloth was highly repellent against D. variabilis for at least 8 days after treatment. 18 In this study, we examined repellency of BioUD against A. americanum for 7 weeks. Mean percentage repellency was > 90% for the first 5 weeks and did not decline significantly until the sixth week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation